Aβ and Inflammatory Stimulus Activate Diverse Signaling Pathways in Monocytic Cells: Implications in Retaining Phagocytosis in Aβ-Laden Environment - Savchenko, Ekaterina; Malm, Tarja; Konttinen, Henna; Hämäläinen, Riikka H.; Guerrero-Toro, Cindy; Wojciechowski, Sara; Giniatullin, Rashid; Koistinaho, Jari; Magga, Johanna (Frontiers in Cellular Neuroscience, 2016)
Background Accumulation of amyloid β (Aβ) is one of the main hallmarks of Alzheimer’s disease (AD). The enhancement of Aβ clearance may provide therapeutic means to restrict AD pathology. The cellular responses to different forms of Aβ in monocytic cells are poorly known. We aimed to study whether different forms of Aβ induce inflammatory responses in monocytic phagocytes and how Aβ may affect monocytic cell survival and function to retain phagocytosis in Aβ-laden environment. Methods Monocytic cells were differentiated from bone marrow hematopoietic stem cells in the presence of macrophage-colony stimulating factor. Monocytic cells were stimulated with synthetic Aβ42 and intracellular calcium responses were recorded with calcium imaging. The formation of reactive oxygen species, secretion of cytokines and cell viability were also assessed. Finally, monocytic cells were introduced to native Aβ deposits ex vivo and the cellular responses in terms of cell viability, pro-inflammatory activation and phagocytosis were determined. The ability of monocytic cells to phagocytose Aβ plaques was determined after intrahippocampal transplantation in vivo. Results Freshly solubilized Aβ induced calcium oscillations, which persisted after removal of the stimulus. After few hours of aggregation, Aβ was not able to induce oscillations in monocytic cells. Instead, lipopolysaccharide (LPS) induced calcium responses divergent from Aβ-induced response. Furthermore, while LPS induced massive production of pro-inflammatory cytokines, neither synthetic Aβ species nor native Aβ deposits were able to induce pro-inflammatory activation of monocytic cells, contrary to primary microglia. Finally, monocytic cells retained their viability in the presence of Aβ and exhibited phagocytic activity towards native fibrillar Aβ deposits and congophilic Aβ plaques. Conclusions Monocytic cells carry diverse cellular responses to Aβ and inflammatory stimulus LPS. Even though Aβ species cause specific responses in calcium signaling, they completely lack the ability to induce pro-inflammatory phenotype of monocytic cells. Monocytes retain their viability and function in Aβ-laden brain.